PENERAPAN METODE BRAINSTORMING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SIKAP PERCAYA DIRI PADA SISWA DI SMP NEGERI 2 NGORO JOMBANG - Vina Zulkarnain; Jumari Jumari (Kampus Akademik Publiser, 2024)
Education plays an important role in improving and developing the quality of human resources. As for a teacher, the success of learning can be seen from the methods used. One of them is the brainstorming method or what can be called brainstorming which can increase students' self-confidence in daring to express their opinions. As is the case at SMPN 2 Ngoro, Brainstorming is considered appropriate for the independent curriculum currently being implemented. This research discusses the Brainstorming Method in Islamic Religious Education Subjects in Increasing Self-Confidence in Students at SMP Negeri 2 Ngoro. The focus of the research is: 1) How to apply the brainstorming method to PAI subjects at SMPN 2 Ngoro Jombang, 2) How to apply the self-confidence of students at SMPN 2 Ngoro Jombang, 3) How to apply the brainstorming method to PAI subjects to increase students' self-confidence at SMPN 2 Ngoro Jombang. This research uses a qualitative approach with a case study type of research. Data collection techniques were carried out using interview, observation and documentation methods. Informants in the research consisted of the Head of Curriculum, Islamic Education Teachers, and Students. Data collected from observations and interviews were analyzed using data validity checking techniques through triangulation analysis techniques. The results of the research that has been carried out show that: 1) the application of the brainstorming method in PAI subjects at SMPN 2 Ngoro, learning is carried out by discussing the material first by the teacher, then presenting and asking questions in groups using mind mapping techniques. 2) The confident attitude of students at SMPN 2 Ngoro can be seen when students are active in class and it reflects that they already have self-confidence, students dare to come forward with presentations, dare to ask questions, are able to answer questions, are able to defend arguments when there are pros and cons from their friends, being able to provide ideas or concepts regarding case studies is part of increasing self-confidence in students. 3) In increasing self-confidence in students at SMPN 2 Ngoro, the teacher gives students the opportunity to ask and answer questions between groups in turn presentations. There are supporting factors that can be seen from adequate infrastructure, professional teachers, and students who are interested in learning. And there are inhibiting factors, namely the lack of closeness between teachers and students, students' social interactions, and students' different backgrounds which have an impact on the quality of students' thinking.